Hand tactile discrimination, social touch and frailty criteria in elderly people: a cross sectional observational study - Vieira, A. I.; Nogueira, D.; Reis, E. D.; Rosado, M. D.; Nunes, M. V.; Castro-Caldas, A. (Archives of Gerontology and Geriatrics, 2016)
Frailty is a common syndrome among elderly and sensory decline may exacerbate functional decline. The hand function, the manual dexterity, the performance of the daily living skills and the social interactions are determined, in a large degree, by sensory integrity. However, hand tactile sensory deterioration has been little explored in frailty. We performed a cross sectional observational study with 181 of institutionalized elders. From the initial sample we selected 50 subjects (68-99 years) who met the inclusion/exclusion criteria. Our goals were (1) to analyse the relationship between tactile discrimination (TD) of the hand, avoidance behaviours and attitudes towards social touch (BATST) and phenotype frailty criteria (unintentional weight loss, self-perception of exhaustion, decrease grip strength - GS, slow walking speed, low level of physical activity), (2) to explore whether other variables can contribute to explain the differences between pre-frail and frail elders. The results showed that increasing age is related to decline of TD of the hand (p = 0.021) and to decrease in GS (p = 0.025); women have significantly lower level of GS (p = 0.001); TD decrease is correlated with higher avoidance BATST (p = 0.000) and with lower GS (p = 0.000); Lower GS corresponds to more avoidance BATST (p = 0.003). Hand TD also can differentiate frail and pre-frail elderly subjects in this sample (p = 0.037). Decreased TD of the hand may have implications on the functionality and on interpersonal relationships. TD of the hand also explains frailty levels in this sample. Hand TD should be used in assessment and intervention protocols in pre-frail and frail elders.